Comparative Study of Economic Benefits of Rain-Fed and Dry Season Farming: Implications for Agricultural Extension in Benue State - P.D., Ivande; A.O , Obademi; A.U., Ugboji (Journal of Home Economics Research, 2024)
The study was a comparative study of economic benefits of rain-fed and dry season farming among rural households. Specifically it identified types of crops cultivated during rain-fed and dry seasons, assessed profit derived from the sale produce at each farming season and other preferred benefits; factors that militating against the practice of dry season farming and identified strategies for improved dry season farming. It was carried out in Makurdi Local Government Area of Benue State with a population of 3379 farm families. A random sample of 350 respondents was selected. Questionnaire was used for data collection. Data were analyzed using mean and standard deviation. Results show different crops cultivated during rain-fed season. Rice was rated as highest cultivated crop(X= 3.79). Vegetables were mostly cultivated during dry season with pumpkin rated as the highest cultivated crop(X=3.81). Dry season farming was more profitable than rain-fed farming. Poor storage facilities was rated as major factor militating against dry season farming, (X=3.5). Provision of water pump generators was suggested by the respondents as the major strategy to improve the practice of dry season farming in the area. It was concluded that dry season farming has more economic benefits to the farmers than rain fed farming.